Implementation of Binaan Inovatif Sehat Mandiri Aktif (BIMA): a community resilience program for COVID-19 at Griya Lare Utami Bantul - Fithriyyah, Yayu Nidaul; Saifudin, I Made Moh. Yanuar; Martani, Hersinta Retno; Arumningtyas, Fajar; Khalish, Gaviota; Ermamilia, Aviria; Wanti, Ipang Fitria; Aulawi, Khudazi; Haryani, Haryani; Kustanti, Anita (Journal of Community Empowerment for Health, 2024)
Introduction: Resilience is the key to overcoming the significant challenges of pandemics or large-scale disasters. Methods: A cross-sectional study design was performed in the study report. The BIMA program implementation lasted from June to November 2022 at Griya Lare Utami, Bantul. DIY, through integrated community services (BIMA): Training (B: Building/Binaan): training for cadres to screen potential health problems, Innovative Activities (I: Inovatif): valid information literacy (anti-hoax) for families and Canva training for youth organizations, Independent of Menu (M: Mandiri menu): Independently develops menus, practical locally available for Small and Medium Enterprise (SME), and Active (A: Aktif); counseling actions, competitions to make fish products, and poster designs, and evaluation of activities for community society. Results: The BIMA program involved 172 people from health cadres (n=12), Youth Organizations (n=24), Innovative Families (n=12), and Small and Medium Enterprises (SME) (n=11), with community members (n=113). The results showed significant differences after the program in cadre roles (p=0.01), Canva training (p=0.01), innovation family training (p=0.04), and knowledge of balanced nutrition (p=0.002). Meanwhile, there was no significant difference in the respondents' understanding regarding the development of local food products after participating in the activity (p=0.082). These results indicate that the BIMA program succeeded in increasing the knowledge and skills of the respondents. Conclusion: The BIMA Program has effectively enhanced the roles of health workers, health literacy, and nutrition management. However, it requires further advancement in the development of local products. It is recommended that the initiative persists with activities aimed at extensive community empowerment, incorporating collaboration with pertinent sectors.